2017
DOI: 10.1080/02713683.2016.1254247
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Mitochondria, Oxidative Stress, and the Radical-binding Protein A1M in Cultured Porcine Retina

Abstract: Purpose: The purpose of this study was to explore the relationship between oxidative stress, antioxidant defense, mitochondrial structure and biomechanical tissue support in the isolated porcine retina. Methods:Full-thickness retinal sheets were isolated from adult porcine eyes. Retinas were cultured for 2 or 48 hours using 1) a previously established low-support explant protocol with photoreceptors positioned against the culture membrane (porous polycarbonate) or 2) a high-support procedure developed by our g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The protective effects of rA1M treatment regarding both elevated BP and oxidative and nitrative stress supports its role as an endogenous radical-scavenging and tissue repair protein 27 . It has been shown that A1M has a protective role against oxidative stress and binds to mitochondria to help maintain morphological structure and ATP production 34,35 . The reduction in kidney expression levels of HO-1 , CAT and SOD2 in the rA1M-treated females supports this protective role, since these are genes involved in responses towards oxidative stress or apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The protective effects of rA1M treatment regarding both elevated BP and oxidative and nitrative stress supports its role as an endogenous radical-scavenging and tissue repair protein 27 . It has been shown that A1M has a protective role against oxidative stress and binds to mitochondria to help maintain morphological structure and ATP production 34,35 . The reduction in kidney expression levels of HO-1 , CAT and SOD2 in the rA1M-treated females supports this protective role, since these are genes involved in responses towards oxidative stress or apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…A1M is considered to be a major factor for progressive impairment of renal function, as well as for early diagnosis of acute allograft rejection [13, 24, 26]. Recent studies have shown A1M to be expressed in rat retinal explants and to have oxygen radical-scavenging and reductase properties; these findings suggest that A1M might protect against oxidative stress and possibly be involved in the response to retinal detachment [27, 28].…”
Section: Lipocalin Family In Humansmentioning
confidence: 99%
“…To establish a functional retinal model, several challenges need to be overcome. A major problem is the limited viability of most retinal organ culture systems due to axotomy or lack of blood flow and biomechanical tissue support leading to metabolic disorders and cell death (Åkerström et al, 2017;Schnichels et al, 2019). This mainly affects RGCs, but also other cell types such as macroglia, displaying gliosis (Tanihara et al, 1997;Wurm et al, 2011;Joachim et al, 2012;Hurst et al, 2017a) and reducing the time frame for experiments with these cultures.…”
Section: Organ Cultures: Advantages and Challengesmentioning
confidence: 99%